Learning science physics is more fun: an exploration of blended learning to stimulate students' critical thinking, lowercase - Cahyandaru, Pramudya; Herman Dwi Surjono; Ali Muhtadi (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
Critical thinking in Natural Sciences (IPA) learning at the elementary school level is essential to develop students' analytical and evaluative abilities. The research discussed in this paper is a systematic literature review related to blended learning, critical thinking, and science published in the last five years. Using scoping reviews, 41 articles were selected for this systematic literature review based on seven research questions. The implications of this conclusion show that applying a constructivist-based blended learning model can improve students' understanding of concepts and learning motivation. However, its success depends on technological readiness, teacher skills, and infrastructure support. To achieve optimal effectiveness, continuous efforts are needed to improve student access to technology, provide intensive training for teachers, and strengthen cooperation between schools, parents, and the government. Without this support, the full potential of blended learning in science learning in elementary schools may be challenging to achieve.